Decolonizing pathways towards integrative healing in social work - Clarke, Kris; Yellow Bird, Michael (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Taking a new and innovative angle on social work, this book seeks to remedy the exclusion of holistic perspectives and rejection of the diversity of human socio-cultural understandings and experiences of healing currently seen in western social work practice. This book examines six areas of healing through an integrative holistic approach that is grounded in a decolonizing perspective. Situating integrative healing within social work education and theory, the book takes an interdisciplinary approach, drawing from social memory and historical trauma, contemplative traditions, storytelling, healing literatures, integrative health, and the traditional environmental knowledge of Indigenous peoples. Exploring issues of movement, play, creativity, animals and the natural world in relation to social work it will appeal to all scholars, practitioners, and community members interested in decolonisation and Indigenous studies"--
Grounding modern social work -- Postcolonial trauma and memory work -- Confronting professional imperialism and moving towards integrative healing -- Water -- Creative expression -- Movement -- Quiet and contemplation -- Fellow creatures -- Mother earth.
OCLC-licensed vendor bibliographic record.
Keywords: Social service; Holistic medicine; SOCIAL SCIENCE / Social Work